Experimental biology of species range dynamics: drivers of survival and dispersal in range-core and range-edge invasive crayfish - Eric Edeline; Agnès Starck; Yoann Bennevault; Jean-Marc Paillisson; Eric J. Petit (Biological Invasions, 2025)

The interaction between warming and enrichment accelerates food‐web simplification in freshwater systems - Willem Bonnaffé; Alain Danet; Camille Leclerc; Victor Frossard; Eric Edeline; Arnaud Sentis (Ecology Letters, 2024)
Nutrient enrichment and climate warming threaten freshwater systems. Metabolic theory and the paradox of enrichment predict that both stressors independently can lead to simpler food‐webs having fewer nodes, shorter food‐chains and lower connectance, but cancel each other's effects when simultaneously present. Yet, these theoretical predictions remain untested in complex natural systems. We inferred the food‐web structure of 256 lakes and 373 streams from standardized fish community samplings in France. Contrary to theoretical predictions, we found that warming shortens fish food‐chain length and that this effect was magnified in enriched streams and lakes. Additionally, lakes experiencing enrichment exhibit lower connectance in their fish food‐webs. Our study suggests that warming and enrichment interact to magnify food‐web simplification in nature, raising further concerns about the fate of freshwater systems as climate change effects will dramatically increase in the coming decades.

Density‐dependent natural selection mediates harvest‐induced trait changes - Alix Bouffet‐Halle; Jacques Mériguet; David Carmignac; Simon Agostini; Alexis Millot; Samuel Perret; Eric Motard; Beatriz Decenciere; Eric Edeline (Ecology Letters, 2021)
Rapid life‐history changes caused by size‐selective harvesting are often interpreted as a response to direct harvest selection against a large body size. However, similar trait changes may result from a harvest‐induced relaxation of natural selection for a large body size via density‐dependent selection. Here, we show evidence of such density‐dependent selection favouring large‐bodied individuals at high population densities, in replicated pond populations of medaka fish. Harvesting, in contrast, selected medaka directly against a large body size and, in parallel, decreased medaka population densities. Five years of harvesting were enough for harvested and unharvested medaka populations to inherit the classically predicted trait differences, whereby harvested medaka grew slower and matured earlier than unharvested medaka. We show that this life‐history divergence was not driven by direct harvest selection for a smaller body size in harvested populations, but by density‐dependent natural selection for a larger body size in unharvested populations.

Pathogens trigger top-down climate forcing on ecosystem dynamics - Eric Edeline; Andreas Groth; Bernard Cazelles; David Claessen; Ian J. Winfield; Jan Ohlberger; L. Asbjørn Vøllestad; Nils C. Stenseth; Michael Ghil (Oecologia, 2016)

Ecological emergence of thermal clines in body size - Eric Edeline; Gérard Lacroix; Christine Delire; Nicolas Poulet; Stéphane Legendre (Global Change Biology, 2013)
The unprecedented rate of global warming requires a better understanding of how ecosystems will respond. Organisms often have smaller body sizes under warmer climates (Bergmann's rule and the temperature‐size rule), and body size is a major determinant of life histories, demography, population size, nutrient turnover rate, and food‐web structure. Therefore, by altering body sizes in whole communities, current warming can potentially disrupt ecosystem function and services. However, the underlying drivers of warming‐induced body downsizing remain far from clear. Here, we show that thermal clines in body size are predicted from universal laws of ecology and metabolism, so that size‐dependent selection from competition (both intra and interspecific) and predation favors smaller individuals under warmer conditions. We validate this prediction using 4.1 × 10 6 individual body size measurements from F rench river fish spanning 29 years and 52 species. Our results suggest that warming‐induced body downsizing is an emergent property of size‐structured food webs, and highlight the need to consider trophic interactions when predicting biosphere reorganizations under global warming.

Four decades of opposing natural and human‐induced artificial selection acting on Windermere pike ( Esox lucius ) - Stephanie M. Carlson; Eric Edeline; L. Asbjørn Vøllestad; Thrond. O. Haugen; Ian J. Winfield; Janice M. Fletcher; J. Ben James; Nils Chr. Stenseth (Ecology Letters, 2007)
The ability of natural selection to drive local adaptation has been appreciated ever since Darwin. Whether human impacts can impede the adaptive process has received less attention. We tested this hypothesis by quantifying natural selection and harvest selection acting on a freshwater fish (pike) over four decades. Across the time series, directional natural selection tended to favour large individuals whereas the fishery targeted large individuals. Moreover, non‐linear natural selection tended to favour intermediate sized fish whereas the fishery targeted intermediate sized fish because the smallest and largest individuals were often not captured. Thus, our results unequivocally demonstrate that natural selection and fishery selection often acted in opposite directions within this natural system. Moreover, the two selective factors combined to produce reduced fitness overall and stronger stabilizing selection relative to natural selection acting alone. The long‐term ramifications of such human‐induced modifications to adaptive landscapes are currently unknown and certainly warrant further investigation.